THE NEW CRITERIA FOR EXPERT EVIDENCE IN BRITISH COURTS – CASE LAW, STATUTORY RULES AND A NEGLIGENCE CASE STUDY - Eisenberg, Paul (PEOPLE: International Journal of Social Sciences, 2018)
This work aims to analyse the legislation proposed by The Law Commission in Great Britain in order to establish statutory criteria for expert evidence in court. The proposal is assessed against the amendment of the Criminal Procedure Rules (CPR) initiated by The Government. From this comparison implications for expert witnesses are derived. For illustrative purposes, the case study of fictitious divorce proceedings of Peter Morgan is dealt with. The study shows legal remedies available to a party against its expert witness in negligence cases. Methodologically, expert evidence admissibility criteria are discussed on the background of common law rules and the Criminal Procedure Rules (2015). Legal academic literature is consulted to enrich the argument. The findings show that the Criminal Procedure Rules (2015) are rooted in settled case law, albeit stressing expertise enhancement and professional qualifications. The discussion of the Peter Morgan case study provides for a legal route for negligence claims based on the case law of Jones v Kaney. The originality of this work is based upon a thorough analysis of case law and legal writings, with the focus on newly introduced Criminal Procedure Rules and recent landmark cases.